Investigating the Potential of Hyperspectral Remote Sensing Data for the Analysis of Urban Imperviousness - a Berlin Case Study. - Linden, Sebastian van der (My University, 2009)
Urbanization is one of the most powerful and irreversible processes by which humans modify the Earth's surface. This work investigates the potential of airborne hyperspectral data to provide information on urban imperviousness that is needed for an integrated analysis of the coupled natural and human systems of urban areas. Based on HyMap imagery from the City of Berlin, Germany, a full image processing workflow is analyzed with regard to accuracy and reliability of resulting map products.
Keywords: Stadtentwicklungsplanung; Bebauung; Dichte; Verdichtung; Versiegelung; Fernerkundung; Verstädterung; Stadtstruktur; Kartierung; Methode; Bebauungsstruktur; Datengewinnung